Social Dynamics in the Northwest Frontiers of the Late Roman Empire Beyond Transformation or Decline - Roymans, Nico; Heeren, Stijn; de Clercq, Wim (Amsterdam Archaeological Studies, 2017)
This volume explores the final phase of the West Roman Empire, particularly the changing interactions between the imperial authority and external 'barbarian' groups in the northwest frontiers of the empire during the fourth and fifth centuries. The contributions present valuable overviews of recent archaeological research combined with innovative theoretical discussions. Key topics include the movement of precious metals, trajectories of imperial power, the archaeology of migration, and material culture in relation to debates about ethnicity.